O REFLECȚIE TEOLOGICĂ ASUPRA RELAȚIEI DINTRE TEHNOLOGIE ȘI LIBERTATEA UMANĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Theological Reflection on the Relationship between Technology and Human Freedom.The purpose of this article is to consider different approaches to technology in relation to different approaches to theology. As society faces the impacts of the information age, the Church must face social changes relevant to its  mission. New digital media are changing the way society communicates ideas  and discovers knowledge. In our current social climate, it is interesting to  consider the impact that digital technology has had on religion.